1998
DOI: 10.1074/jbc.273.24.14707
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cytotoxicity of Nucleoside Analogs by Overexpression of Mitochondrial Deoxyguanosine Kinase in Cancer Cell Lines

Abstract: The cytotoxic anti-cancer purine nucleoside analogs 2-chloro-2-deoxyadenosine (CdA), 9-␤-D-arabinofuranosylguanine (araG), and 2,2-difluorodeoxyguanosine (dFdG) are phosphorylated by human mitochondrial deoxyguanosine kinase (dGK) in vitro. We overexpressed dGK as a fusion protein to the green fluorescent protein in the human pancreatic cancer cell lines PanC-1 and MIA PaCa-2 to determine the importance of dGK-mediated nucleoside analog phosphorylation. The transfected cells showed mitochondrial fluorescence p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…A low but significant activity with ganciclovir was also observed with the recombinant enzyme (24), similar to what was reported earlier with native dGK (25). This low activity may be involved in the toxicity observed with ganciclovir (26), although it is not clear how a mitochondrial enzyme can be responsible for the toxicity of nucleoside analogs, which supposedly target nuclear DNA synthesis (35).…”
supporting
confidence: 61%
“…A low but significant activity with ganciclovir was also observed with the recombinant enzyme (24), similar to what was reported earlier with native dGK (25). This low activity may be involved in the toxicity observed with ganciclovir (26), although it is not clear how a mitochondrial enzyme can be responsible for the toxicity of nucleoside analogs, which supposedly target nuclear DNA synthesis (35).…”
supporting
confidence: 61%
“…The mutant NDP kinase could then play the role of a suicide enzyme in case of uncontrolled proliferation (31,32). The overexpression of the mitochondrial deoxyguanosine kinase in human pancreatic adenocarcinoma cell lines was reported to enhance sensitivity of the cells to CdA, araG, and dFdG (33). Promising results have already been obtained by transfection with herpes simplex thymidine kinase that increases the cells sensitivity to ganciclovir (34).…”
Section: Fig 4 Structure Of Ei-n119s In Complex With Rb-azt-tpmentioning
confidence: 58%
“…A possible explanation is that up-or down-regulation of nucleoside metabolizing enzymes in our HEK293 cells limits the potential for transport by MRP4 or MRP5. On the one hand, the toxicity of gemcitabine, cytarabine, and cladribine in cell lines increases proportionally with deoxycytidine kinase activity (Galmarini et al, 2001), and transfection with mitochondrial deoxyguanosine kinase has also been shown to increase sensitivity to the cytostatic activity of these agents (Zhu et al, 1998). On the other hand, transfection with human cytosolic nucleotidase imparts HEK293 cells with resistance against cladribine and gemcitabine (Hunsucker et al, 2001), and we have previously found that thiopurine nucleotides were rapidly dephosphorylated in HEK293 cells, limiting the toxicity of thiopurine drugs (Wielinga et al, 2002).…”
Section: Discussionmentioning
confidence: 99%